2016
DOI: 10.1007/s10557-016-6676-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Angina Pectoris Associated with Coronary Microvascular Dysfunction

Abstract: Treatment of angina pectoris associated with coronary microvascular dysfunction is challenging as the underlying mechanisms are often diverse and overlapping. Patients with type 1 coronary microvascular dysfunction (i.e. absence of epicardial coronary artery disease and myocardial disease) should receive strict control of their cardiovascular risk factors and thus receive statins and ACE-inhibitors in most cases. Antianginal medication consists of ß-blockers and/or calcium channel blockers. Second line drugs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…. We found that ranolazine did not improve CFR, and other studies have yielded similar findings (23,26,(69)(70)(71). However, some studies indicate that ranolazine may improve the coronary microvascular function by improving angina symptoms (18,72).…”
Section: )supporting
confidence: 78%
“…. We found that ranolazine did not improve CFR, and other studies have yielded similar findings (23,26,(69)(70)(71). However, some studies indicate that ranolazine may improve the coronary microvascular function by improving angina symptoms (18,72).…”
Section: )supporting
confidence: 78%
“…Numerous studies indicate an increased risk of cardiovascular events in these patients and high costs due to frequent rehospitalization, repeat diagnostic procedures, and medical therapy [ 1 ••, 4 , 5 ]. Approximately one third of patients remain symptomatic in spite of therapeutic interventions, which are often empirical [ 5 , 6 •]. NOCAD angina is associated with depression and decreased quality of life (QoL) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…ACS based on the pathological basis of rupture or invasion of atherosclerotic plaque and subsequent complete or incomplete occlusive thrombosis included the acute T-segment elevation myocardial infarction, acute non-ST-segment elevation myocardial infarction and unstable angina (16). Cardiac syndrome X, also known as microvascular angina, is defined as angina pectoris caused by abnormalities of the small coronary arteries, and is characterized by the patient experiencing chest pain during exercise and evidence of myocardial ischemia with a non-invasive stress test (17). With these patients the coronary angiography can appear normal (18).…”
Section: Methodsmentioning
confidence: 99%